2010
DOI: 10.1128/jcm.00896-09
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Threshold for a Positive Hybrid Capture 2 Test for Detection of Human Papillomavirus: Data from the ARTISTIC Trial

Abstract: We present data on the use of the Hybrid Capture 2 (HC2) test for the detection of high-risk human papillomavirus (HR HPV) with different thresholds for positivity within a primary screening setting and as a method of triage for low-grade cytology. In the ARTISTIC population-based trial, 18,386 women were screened by cytology and for HPV. Cervical intraepithelial neoplasia lesions of grade two and higher (CIN2؉ lesions) were identified for 453 women within 30 months of an abnormal baseline sample. When a relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 15 publications
3
55
0
Order By: Relevance
“…[24][25][26][27][28][29] The recently published series from Sargent et al 29 reported a reduced rate of high-grade dysplasia after an hrHPV test, with an RLU/CO value of between 1 and 2 (ie, 9.2% vs 17.9% for an RLU/CO value 2.0), although their methodology differs considerably from that of the current present study (eg, combining ''borderline'' and ''mild'' cytology). Nevertheless, the indicated rate of 9.2% represents a nearly 5-fold risk compared with that associated with negative hrHPV tests in the study by Sargent et al 29 Using polymerase chain reaction-based hrHPV detection, an increase in the viral load of carcinogenic subtypes demonstrates a positive correlation with cervical abnormalities in the general population (ie, when all Pap diagnoses are included), 26 and the association between type-specific HPV-16 viral load with CIN III or cancer indicates a positive correlation in patients with negative cervical cytology, but not those with ASC-US cytology. 24 When HC II was used to detect hrHPV subtypes, no association was noted between increasing viral load and the risk of CIN III or cancer, 27 although a modest positive correlation was observed for CIN I.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29] The recently published series from Sargent et al 29 reported a reduced rate of high-grade dysplasia after an hrHPV test, with an RLU/CO value of between 1 and 2 (ie, 9.2% vs 17.9% for an RLU/CO value 2.0), although their methodology differs considerably from that of the current present study (eg, combining ''borderline'' and ''mild'' cytology). Nevertheless, the indicated rate of 9.2% represents a nearly 5-fold risk compared with that associated with negative hrHPV tests in the study by Sargent et al 29 Using polymerase chain reaction-based hrHPV detection, an increase in the viral load of carcinogenic subtypes demonstrates a positive correlation with cervical abnormalities in the general population (ie, when all Pap diagnoses are included), 26 and the association between type-specific HPV-16 viral load with CIN III or cancer indicates a positive correlation in patients with negative cervical cytology, but not those with ASC-US cytology. 24 When HC II was used to detect hrHPV subtypes, no association was noted between increasing viral load and the risk of CIN III or cancer, 27 although a modest positive correlation was observed for CIN I.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the test specificity, several studies have implemented a higher cut-off for the positivity of HPV DNA testing. 8 However, these trials caused a decrease in sensitivity and negative predictive value (NPV), and no cut-off level could exclude patients with underlying CIN2/CIN3 lesions or cancer. However, the use of viral load as a predictor of high-grade cervical lesions in women with ASC-US cytology is doubtful, because of the large overlap of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…On the spectrum of cervical disease, CIN2 and 3 are considered cervical cancer precursors. Several studies have consistently reported that the persistence of HR-HPV in the genital tract is necessary for the development and progression of cervical dysplastic lesions (Ho et al, 1995;Remmink et al, 1995;Nobbenhuis et al, 1999;Briolat et al, 2007;Xi et al, 2008;Sargent et al, 2010). Conversely, high-grade squamous intraepithelial lesions were shown to be unlikely to develop in HR-HPVnegative women in a 2-year follow-up cohort, and smears showed that mild or borderline cell atypia returns to normal (Nobbenhuis et al, 2001;Zielinski et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Specimens with a ratio of <1.00 were considered to be negative, and those with a ratio of ≥1.00 were considered to be positive because they contained at least 1 pg/mL HPV DNA, equivalent to 100,000 HPV copies/mL or 5000 HPV copies/assay (Sargent et al, 2010).…”
Section: Molecular Analysismentioning
confidence: 99%